Effects of different ergogenic agents on athlete`s mental/ physiological performance test rates - Tambovtseva, R. V.; Sechin, D. I. (Theory and Practice of Physical Culture, 2019)
Modern athletic training systems give a high priority to efficient ergogenic agents to improve the competitive fitness. One of the key criteria in the ergogentic agent selection process, in addition to its safety and efficiency, is its origin. The study was designed to rate the short-time effects on the athletes` mental and physiological test rates of neuropeptide Semax 0.1% versus the hypoxic training by 10% oxygen mix. Sampled for the experiment were the 21-25 year old highly skilled (CMS+) athletes representing different sports (n=45) split up into Reference Group, Semax Group and Hypoxia Group. The experiment was run from 09:00 AM to 12:00, with the meals allowed for 3+ hours prior to the experiment. The Reference Group administered intranasal NaCl; Semax Group administered 500mg of Semax 0.1%; and the Hypoxia Group was subject to 30min hypoxic trainings by 10% oxygen mix. The ergogenic effects on the athletes` mentality and physiology were rated by the following tests: response to beep; response to flash; choice reaction; individual minute; and the interval (six 10s intervals) tapping (TT1-TT6) test. The Semax Group and Hypoxia Group were tested with the similar benefits of both ergogenic agents (despite the difference in their bodily `targets`) as verified by response tests.